Transformation of gels via catalyst-free selective RAFT photoactivation. Issue 19 (15th April 2019) - Shanmugam, Sivaprakash; Cuthbert, Julia; Flum, Jacob; Fantin, Marco; Boyer, Cyrille; Kowalewski, Tomasz; Matyjaszewski, Krzysztof
Abstract : This work explores the concept of structurally tailored and engineered macromolecular (STEM) networks by proposing a novel metal-free approach to prepare the networks. Abstract : This work explores the concept of structurally tailored and engineered macromolecular (STEM) networks by proposing a novel metal-free approach to prepare the networks. STEM networks are composed of polymer networks with latent initiator sites affording post-synthesis modification. The proposed approach relies on selectively activating the fragmentation of trithiocarbonate RAFT agent by relying on visible light RAFT iniferter photolysis coupled with RAFT addition–fragmentation process. The two-step synthesis explored in this work generates networks that are compositionally and mechanically differentiated than their pristine network. In addition, by careful selection of crosslinkers, conventional poly(ethylene glycol) dimethacrylate ( M n = 750) or trithiocarbonate dimethacrylate crosslinker (bis[(2-propionate)ethyl methacrylate] trithiocarbonate (bisPEMAT)), and varying concentrations of RAFT inimer (2-(2-( n -butyltrithiocarbonate)-propionate)ethyl methacrylate (BTPEMA)), three different types of primary (STEM-0) poly(methyl methacrylate) (PMMA) networks were generated under green light irradiation. These networks were then modified with methyl acrylate (MA) or N, N -dimethylacrylamide (DMA), under blue light irradiation to yield STEM-1 gels that are either stiffer or softer with different responses to polarity (hydrophilicity/hydrophobicity).